2018
DOI: 10.1136/jnnp-2017-317341
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of symptomatic intracranial haemorrhage in patients with an ischaemic stroke with neurological deterioration after intravenous thrombolysis

Abstract: Change in level of consciousness is associated with sICH among patients undergoing emergent brain imaging after receiving tPA. In this group of patients, preparation of tPA reversal agents while awaiting brain imaging may reduce reversal times. Future studies are needed to study the cost-effectiveness of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…This frequency and proportion of END was comparable to previous studies in which 0.9 mg/kg alteplase was administrated [1, 2, 7, 9, 13, . The median time from administration of rt-PA to deterioration was 8 h for END h and 4 h for END i , and mainly occurred within first 2 h. Similar results were reported in a recent study in which END occurred at a mean of 7.3 h after rt-PA administration in patients with sICH, and 4.8 h in those without [15]. Moreover, ERIS has been reported to occur during or shortly after rt-PA administration [5,6].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This frequency and proportion of END was comparable to previous studies in which 0.9 mg/kg alteplase was administrated [1, 2, 7, 9, 13, . The median time from administration of rt-PA to deterioration was 8 h for END h and 4 h for END i , and mainly occurred within first 2 h. Similar results were reported in a recent study in which END occurred at a mean of 7.3 h after rt-PA administration in patients with sICH, and 4.8 h in those without [15]. Moreover, ERIS has been reported to occur during or shortly after rt-PA administration [5,6].…”
Section: Discussionsupporting
confidence: 87%
“…Univariate analyses of clinical characteristics between non-END patients and patients with END h and END i are shown in Table 1. Compared with non-END patients, the extensive EIC and large artery occlusions were more common in patients with both END subtypes; the pretreatment NIHSS score was higher (20.5 [16][17][18][19][20][21][22][23][24][25][26] vs. 14 [8][9][10][11][12][13][14][15][16][17][18][19][20], p = 0.001) and pretreatment with antiplatelets was more common (50.0% vs. 27.7%, p = 0.022) in patients with END h , and AF was more common in patients with END i (64.9% vs. 49.3%, p = 0.027). The multivariate analyses revealed that a higher pretreatment NIHSS score (odds ratio [OR] 1.06, 95% confidence interval [CI] 1.00-1.13) and pretreatment with antiplatelets (OR 2.84, 95% CI 1.08-7.72) were associated with END h .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most deterioration related to intracerebral haemorrhage occurred after the complete rtPA infusion, and deterioration was four times more likely to be due to initial ischaemia rather than to intracerebral haemorrhage. 65 Deteriorating patients need urgent repeat neuroimaging to clarify the cause and rtPA infusion is usually suspended pending imaging.…”
Section: Introductionmentioning
confidence: 99%
“…From a prospective stroke database, the only predictor of SICH was the change in the level of consciousness, which happened in 108 out of 511 patients and 19 of them had SICH (odds ratio [OR]: 6.62; 1.64–26.7). [30]…”
Section: Introductionmentioning
confidence: 99%